Climate Risk and Capital Structure - Ginglinger, Edith; Moreau, Quentin (Management Science, 2023)
We use firm-level data that measure forward-looking physical climate risk to examine the impact of climate risk on capital structure. We find that greater physical climate risk leads to lower leverage in the post-2015 period (i.e., after the Paris Agreement and the first step of standardization of disclosure of climate risk information). Our results hold after controlling for firm characteristics known to determine leverage, including credit ratings. Our evidence shows that the reduction in leverage related to climate risk is shared between a demand effect (the firm’s optimal leverage decreases) and a supply effect (bankers and bondholders increase spreads when lending to firms with the greatest risk). Our results are consistent with the hypothesis that physical climate risk affects leverage via larger expected distress costs and higher operating costs. This paper was accepted by Colin Mayer, Special Section of Management Science on Business and Climate Change. Funding: This project benefited from the financial support of the Institut Europlace de Finance (Grant EIF 2019). Q. Moreau acknowledges financial support from the French Association of Institutional Investors. The authors have received in-kind support from Carbone 4 for this project in the form of a data set of climate risk ratings. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.4952 .